To be GMP or not to be– a radionuclide’s question - Clemens Decristoforo; Renata Mikolajczak; Clive Naidoo; Suzanne Lapi; Ferid Haddad; David Emmanuel Schmid; Lurdes Gano; Ulli Köster; Thierry Stora (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Radionuclides are the essential component of radiopharmaceuticals, their production needs to consider pharmaceutical regulations and guidelines, also for clinical research applications. Main body In this paper we reflect on the pharmaceutical regulatory landscape for radionuclide production in Europe, with a focus on Good Manufacturing Practices (GMP). The challenges for novel production pathways and the pathways for non-GMP production of radionuclides are discussed. Conclusion In particular when radionuclides are used as starting materials, exemptions from GMP requirements are essential for clinical innovation and a common understanding is needed to enable the safe use of novel radionuclides for medical applications without unnecessary regulatory hurdles for the user.